Factors associated with water consumption among children: a systematic review - Carmen B. Franse; L. Wang; Florence Constant; Lisa R. Fries; Hein Raat (BMC, 2019)
Abstract Background Water is recommended as the main beverage for daily fluid intake. Previous systematic reviews have studied the consumption of sugar-sweetened beverages (SSBs) among children, but none have focused on water consumption. Insight into factors that are associated with children's water intake is needed to inform the development of interventions aimed at the promotion of water consumption. The objective of this review was therefore to summarize the current evidence on factors associated with water consumption among children aged 2 to 12 years. Methods A systematic literature search in seven electronic databases was conducted in May, 2018 and retrieved 17,850 unique records. Two additional studies were identified by hand-searching references of included articles. Studies were selected if they had a cross-sectional or longitudinal study design, focused on children aged 2-12 years and published in an English language peer-reviewed journal. Participants from clinical populations, studies that included data of < 10 participants and non-human studies were excluded. Results A total of 63 articles met inclusion criteria and were included in the analysis. We identified 76 factors that were investigated in these studies; 17/76 were investigated in a longitudinal study. There was evidence of positive associations between water consumption and child's self-efficacy, parental education level, parental self-efficacy, use of feeding practices such as restriction or encouraging healthy eating and study year. Evidence was inconsistent (< 60% of studies reported an association) for child's age, sex, BMI, consumption of SSBs and ethnic background of the parent. There was no evidence (≤33% of studies reported an association) of associations between consumption of milk or juice, parental emotional-, modelling- or instrumental feeding practices, eating school lunch or outside temperature and water consumption. The remaining 54 factors were investigated in fewer than three studies. Conclusions There is some evidence for an association between potentially modifiable parental and child-related factors and water consumption. However, most factors identified in this review were only studied by one or two studies and most studies were cross-sectional. More longitudinal research is necessary to investigate environmental, parental and child-related factors associated with water consumption that are currently under-studied and could further inform intervention strategies. Trial registration PROSPERO ID# CRD42018093362, registered May 22, 2018.